E-LIBRARY OF A TECHNICAL UNIVERSITY: PROBLEMS AND PROSPECTS - Olga B. Shamina; Irina V. Kotova (Moscow Polytechnic University, 2022)
The paper presents an analysis of the scientific and educational resources of Tomsk Polytechnic University, first of all, there are discussing the different types of training materials developed by the staff of the University. In conditions of open education the information is rapidly changing. Thus, the educational content should not only be available to students in accordance with the requirements of the Federal Service for education and science, but also become the most convenient when working in remote access.